(untitled) (Journal of Dhaka Medical College, 2011)
Context: Cervical plexus block anaesthetizes the pain sensitive structures in the neck, shoulder and skin of upper chest up to sternal angle which is suitable for operations in the neck and shoulder, particularly on the thyroid gland. It may also be used as a modality of pain therapy in this region. The aim the study was to find out the advantages and disadvantages of thyroid surgery under regional anaesthesia i.e. cervical plexus block. Methods: Nine cases of thyroid disorders were operated in Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital, Dhaka, over a period of 18 months from July 2008 to September 2010, where lobectomy was done in 2 cases, hemithyroidectomy in 4 cases, isthmusectomy in 1 case, subtotal thyroidectomy in 1 case and total thyroidectomy in 1 case. Results: The advantages that we observed were less bleeding, time saving procedure, avoidance of endotracheal intubation, physical ability of the patient to take food and drink immediately at post operative period and early mobility of the patient after the operation. The only disadvantage that we faced was temporary dysphagia in one case. Key words: Cervical plexus block; regional anaesthesia; thyroid surgery. DOI: 10.3329/jdmc.v19i2.7072 J Dhaka Med Coll. 2010; 19(2) : 76-79